2006
DOI: 10.1111/j.1600-0447.2005.00745.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitude towards antipsychotics among out‐patients with schizophrenia in Nigeria

Abstract: Special attention should be paid to patients with these factors while designing programmes to improve overall compliance in patients with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
64
7

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 35 publications
13
64
7
Order By: Relevance
“…This decision would be based on the belief that Western medicine provides a rapid palliative action, whereas traditional Chinese medicine is believed to produce a slow but curative or prophylactic action [22]. We presumed that subjects in Beijing had more negative attitudes toward medication due to a higher employment rate; because employment was associated with negative attitudes toward medication in previous studies [29][30][31]. However this hypothesis was not supported by our data.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…This decision would be based on the belief that Western medicine provides a rapid palliative action, whereas traditional Chinese medicine is believed to produce a slow but curative or prophylactic action [22]. We presumed that subjects in Beijing had more negative attitudes toward medication due to a higher employment rate; because employment was associated with negative attitudes toward medication in previous studies [29][30][31]. However this hypothesis was not supported by our data.…”
Section: Discussioncontrasting
confidence: 57%
“…Previous reports from Western or African countries have revealed that subjective responses to medication were associated with side effects [29,31,32], psychopathology [18,29,[31][32][33], and employment status [29][30][31], but were independent of other sociodemographic variables or length of illness [18,[30][31][32][33][34]. In this study, however, age and gender (China) and length of illness (Japan), were significantly associated with DAI-30, but employment status showed no significant association.…”
Section: Discussioncontrasting
confidence: 54%
“…Several studies have shown that a negative attitude toward medication was associated with the presence of symptoms [9,30] and global psychopathology [25,26,29,32]. But this study showed that drug attitude was not affected significantly by global psychopathology, as assessed by the CGIS Scale.…”
Section: Discussioncontrasting
confidence: 73%
“…Employment was a significant predictive factor for positive attitude [29], but other studies have revealed that employment was a significant predictive factor for negative attitude [9,25,30,31]. In this study, we found that drug attitude was not affected significantly by occupational status.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation